The Prevalence of Nurses’ Emotional Exhaustion during COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Rana Alaseeri; Omar Ghazi Baker; Maram Banakhar (Department of Nursing, Faculty of Medicine, Diponegoro University, 2023)
Background: Nurses in many countries face a high prevalence of psychological pressure while caring for COVID-19 patients. Several determinants of emotional exhaustion leading to occupational burnout risk were documented. However, a recent review examining nurses’ emotional exhaustion during the COVID-19 pandemic is lacking in nursing literature.Purpose: This review aimed to examine the prevalence of nurses’ emotional exhaustion during the COVID-19 pandemic. This review also describes the organizational contributing factors to nurses’ emotional exhaustion.Methods: A systematic review and meta-analysis of the literature following the PRISMA guidelines was conducted in March 2022. Four databases, including PubMed, ProQuest Platform, Wiley, and Google Scholar, were searched from 1 January 2020 to 28 February 2022. The prevalence of nurses’ emotional exhaustion (EE) was pooled using random effect meta‐analyses. The quality appraisal of the studies was done using the Joanna Briggs Institute (JBI) checklist. Data analysis utilized a random effect model to evaluate the pooled effects of the studies due to the high heterogeneity between results.Results: Nine studies were included with a total number of 16,810 subjects surveyed, of whom, 8,150 (48.50%) met the criteria for emotional exhaustion. Based on the standard effect model, the pooled estimate for EE prevalence was 48.9% (95% CI:48.1% to 49.6%). Several organizational factors contributing to nurses’ emotional exhaustion included working in critical care units or isolation wards, longer working hours in COVID-19 quarantine units, night shifts, working with confirmed or suspected co-workers, monthly salary income, and inadequate hospital resources.Conclusion: This review found that nurses were suffering from high to moderate emotional exhaustion levels during the COVID-19 pandemic. Furthermore, several organizational factors influence this emotional exhaustion. These findings highlight the necessity for urgent interventions to decrease psychological impacts on frontline nurses.